CLDN5: From structure and regulation to roles in tumors and other diseases beyond CNS disorders - Yao Ling; Xinxin Kang; Ying Yi; Shenao Feng; Guanshen Ma; Huinan Qu (Elsevier, 2024)
Claudin-5 (CLDN5) is an essential component of tight junctions (TJs) and is critical for the integrity of the blood-brain barrier (BBB), ensuring homeostasis and protection from damage to the central nervous system (CNS). Currently, many researchers have summarized the role and mechanisms of CLDN5 in CNS diseases. However, it is noteworthy that CLDN5 also plays a significant role in tumor growth and metastasis. In addition, abnormal CLDN5 expression is involved in the development of respiratory diseases, intestinal diseases, cardiac diseases, and diabetic ocular complications. This paper aims to review the structure, expression, and regulation of CLDN5, focusing on its role in tumors, including its expression and regulation, effects on malignant phenotypes, and clinical significance. Furthermore, this paper will provide an overview of the role and mechanisms of CLDN5 in respiratory diseases, intestinal diseases, cardiac diseases, and diabetic ocular complications.